Physiotherapeutic treatments for neurogenic bladder: a literature review (Research, Society and Development, 2021)
Neurogenic Bladder is classified as a dysfunction of the lower urinary tract resulting from interruption of the nerve roots, with vesico-sphincter alterations and disturbances in the filling and emptying phases. Its symptoms include urinary urgency, increased frequency of daytime urination, nocturia, and also the absence or presence of urinary incontinence, which reflect both on the patient's physical and mental health and on their social life. Considering the symptoms of the pathology, this study is a literature review, which sought to list the physical therapy treatments available in the literature. Searches were carried out in the Cochrane, Scientific Electronic Library Online (SciELO), LILACS, PhysiotherapyEvidenceDetabase (PEDro) databases. The results highlighted the physical therapy techniques that showed positive results for the Neurogenic Bladder, among them, electrostimulation in the sacral region and peripheral nerves, interferential electrical stimulation, electroacupuncture, combined therapy, training for pelvic support muscles and bipolar radiofrequency. It is concluded that physiotherapy has proven to be effective in symptoms of BN, with methods that are easily accepted and adaptable to patients, providing benefits and better quality of life for this audience.